2021
DOI: 10.1134/s1063785021080058
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Energy Efficiency of Ignition of a Fuel Mixture by Spark and Streamer Discharges

Abstract: An increase in fuel efficiency and efficiency of combustion processes in power plants is discussed based on the data of physical and computational experiments.Two systems for ignition of a fuel mixture are considered, one of which uses a multipoint pulsed spark discharge, and the other uses a multipoint streamer discharge. A comparative assessment of the energy efficiency of each approach to the ignition of the air/fuel mixture is carried out, and conclusions are drawn about their effectiveness and prospects f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Initiators were half-wave linear vibrators in the form of metal wire segments with rounded ends and were located on the axis of the chamber and simultaneously parallel to the polarization vector of microwave radiation. The results of studies carried out in papers [1][2][3], demonstrated the possibility in principal to implement microwave ignition systems in high-pressure combustion chambers and their prospects. At the same time, the initiated microwave discharges were in the form of single streamers of limited length, which is explained by the short duration of radiation source pulses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initiators were half-wave linear vibrators in the form of metal wire segments with rounded ends and were located on the axis of the chamber and simultaneously parallel to the polarization vector of microwave radiation. The results of studies carried out in papers [1][2][3], demonstrated the possibility in principal to implement microwave ignition systems in high-pressure combustion chambers and their prospects. At the same time, the initiated microwave discharges were in the form of single streamers of limited length, which is explained by the short duration of radiation source pulses.…”
Section: Introductionmentioning
confidence: 99%
“…Use of initiated microwave discharges for ignition of combustible mixtures in the high-pressure chamber makes it possible to both create such discharges at significantly lower power of a microwave energy source, but also to localize them in the working chamber in the right place [1]. Comparative studies of the process of combustible mixture ignition by spark discharge from plugs of standard configuration and initiated microwave discharges were carried out in paper [2]. The study results demonstrated that ignition using a microwave discharge is much more energy efficient than the spark one [3].…”
Section: Introductionmentioning
confidence: 99%